Nanocellulose-based Janus particles and preparation method and application thereof
Through a simplified process, the Janus particle compatibilizer used in the thermoplastic polyurethane/butyl rubber blending system was prepared, which solved the problem of complex and high cost of the existing Janus nanoparticle preparation process, and achieved efficient and low-cost preparation and excellent capacitance effect.
Patent Information
- Application Number
- CN202411947883.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
AI Technical Summary
The existing Janus nanoparticles have complex preparation processes, using a large number of organic solvents, which are costly and unfavorable to the environment, limiting their industrial application potential, especially in situations where large-scale production is required.
Nanocellulose-based Janus particles were prepared by reacting isocyanate-based nanocellulose with epoxidized butyl rubber and used as a compatibilizer for thermoplastic polyurethane/butyl rubber incompatible polymer blends. The process is simple and suitable for large-scale industrial production.
It realizes efficient preparation of Janus nanoparticles, reduces production costs, improves the mechanical properties and heat resistance of composite materials, expands its application range, and has good practical utilization value.
Smart Images

Figure BDA0005214146470000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials and rubber and plastic processing, and in particular to a Janus particle based on nanocellulose and a preparation method and application thereof. Background Art
[0002] In the field of materials science, Janus nanoparticles have attracted much attention due to their unique surface chemical structure and functional properties. The surface of Janus particles is precisely modified with different groups or molecular chains, so they exhibit dual properties. This unique property makes their adsorption energy at the interface extremely high, and they are widely used in the expansion of incompatible blends. By rationally designing the surface structure of Janus particles, the compatibility of the blend can be effectively improved and the overall performance of the material can be enhanced.
[0003] Among the published patents, Chinese patent 202410701434.8 provides a Janus particle crosslinker and a two-step preparation method and application thereof. The solution converts SiO 2 One end of the particle was modified with a hydrophilic group, the isocyanate group, and the other end was modified with a low surface energy substance, hydrogenated silicone oil. A Janus particle crosslinker with hydrogenated silicone oil as the hydrophobic side was successfully prepared. The crosslinker can be arranged in a directional manner, thereby giving the coating excellent hydrophobic properties. In addition, the isocyanate group in the Janus particle crosslinker can not only play a crosslinking role in the coating, but also stabilize the toluene / water Pickering emulsion, demonstrating the application potential of Janus particles in multiple fields.
[0004] Another Chinese patent 201710985945.7 proposes a Janus compatibilizer for rubber toughened epoxy resin and its preparation method. The scheme is based on a two-step preparation method, in which dodecyl mercaptan-polydivinylbenzene and methacryloxypropyltrimethoxysilane are grafted onto the surface of silica to obtain anisotropic Janus particles. This Janus particle has rich interfacial behavior, which can effectively promote the compatibility between liquid isoprene rubber and epoxy resin and improve the overall performance of the composite material.
[0005] Although Janus nanoparticles have shown great application potential in the fields of cross-linking and volume expansion, their preparation process is relatively complicated. The current mainstream preparation methods of Janus nanoparticles often involve the use of a large amount of organic solvents, long-term reactions and heating processes, which not only increase production costs, but also cause many adverse effects on the environment. In addition, the complex preparation process also limits the industrial application potential of Janus nanoparticles, especially in situations where large-scale production is required. Therefore, it is particularly important to develop a Janus nanoparticle with a simple preparation process, low cost and suitable for a specific blending system in view of this situation. Summary of the invention
[0006] One of the purposes of the present invention is to provide a Janus particle based on nanocellulose, wherein the Janus particle is specifically nanocellulose with isocyanate group and butyl rubber modified at both ends respectively.
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned Janus particles, comprising: mixing and reacting isocyanate-based nanocellulose and epoxidized butyl rubber (EIIR) to obtain nanocellulose-based Janus particles.
[0008] Furthermore, the preparation method of isocyanate nanocellulose is as follows: carboxylated nanocellulose (C-CNC) is uniformly mixed with isocyanate propyltriethoxysilane and a solvent, the obtained mixture is heated and fully reacted, and solid-liquid separation is performed to obtain isocyanate nanocellulose.
[0009] Furthermore, the solvent is specifically a mixture of deionized water and xylene, and the mass ratio of the two is 10-100:10-100.
[0010] Furthermore, the mass ratio of carboxylated nanocellulose, isocyanate propyltriethoxysilane and solvent required for the reaction is 1-20:1-20:20-200.
[0011] Furthermore, after the addition is completed, the carboxylated nanocellulose, isocyanate propyltriethoxysilane and solvent are evenly mixed by ultrasound, and the obtained mixture is heated to a reaction temperature of 40-70° C. After the reaction, the isocyanate nanocellulose is obtained by centrifugal separation, washing and drying.
[0012] Furthermore, the mass ratio of isocyanate-based nanocellulose to epoxidized butyl rubber is 1-20:1-20.
[0013] Furthermore, after the isocyanate-based nanocellulose and the epoxidized butyl rubber are mixed, they are heated to 170-230° C. for high-temperature melt blending while stirring (rotation speed 20-100 rpm), and then naturally cooled to room temperature to obtain nanocellulose-based Janus particles.
[0014] The third object of the present invention is to provide the use of the above-mentioned Janus particles as a compatibilizer in a thermoplastic polyurethane-butyl rubber incompatible polymer blend.
[0015] Furthermore, the specific method of the application is as follows: thermoplastic polyurethane or butyl rubber is mixed with the Janus particles, and then butyl rubber or thermoplastic polyurethane is added and heated to melt and blend, and then naturally cooled.
[0016] Furthermore, the mass ratio of thermoplastic polyurethane to butyl rubber is (10-X):(X), and the value range of X is 1-4 (including the endpoints).
[0017] Furthermore, the mass ratio of thermoplastic polyurethane to butyl rubber is preferably 7:3.
[0018] Furthermore, the amount of Janus particles added is equivalent to 0.5%-5% of the total mass of the thermoplastic polyurethane and the butyl rubber, preferably 1%-5wt%.
[0019] Furthermore, the melt blending temperature is 170-240°C.
[0020] The compatibility of thermoplastic polyurethane and butyl rubber is poor, and traditional volume expansion methods are often difficult to achieve ideal results. Therefore, a Janus nanoparticle expander with excellent volume expansion effect and simple preparation process is developed, and used in thermoplastic polyurethane / butyl rubber blending system, which is of great significance for improving the overall performance of composite materials, reducing production costs and promoting the sustainable development of related industries. The two ends of the Janus particles prepared by the present invention can respectively interact with the thermoplastic polyurethane and butyl rubber phases. Specifically, the butyl rubber molecular chain in the Janus particles is closely connected with the rubber phase in the blending system through the molecular chain entanglement, and the isocyanate group produces a strong intermolecular interaction with the thermoplastic polyurethane. This design enables the modified Janus nanoparticle expander to be accurately phased and arranged at the interface of the two phases, effectively promoting the mutual fusion and synergy between the two phases.
[0021] Compared with existing similar products or technologies, the improved effects of the present invention are mainly reflected in the following aspects:
[0022] (1) A new type of Janus particle was prepared by modifying one end of nanocellulose with a hydrophilic group of isocyanate and the other end with butyl rubber, and used as a compatibilizer for butyl rubber / thermoplastic polyurethane incompatible polymer blends. The Janus particles can be evenly arranged at the interface of butyl rubber and thermoplastic polyurethane, thereby improving the interfacial bonding between the two phases of the matrix polymer and promoting the transfer of force at the interface, ultimately improving the physical and mechanical properties of the blend.
[0023] (2) The unique double molecular chain structure on the surface of Janus nanoparticles enables them to exhibit excellent capacity for increasing the volume of thermoplastic polyurethane / butyl rubber blends. This structure not only enhances the interaction between the particles and the polymer molecular chains, but also significantly improves the overall performance of the blends, such as mechanical strength, hardness and heat resistance, thus providing a broader space for the application of thermoplastic polyurethane / butyl rubber blends.
[0024] (3) The method for synthesizing Janus nanoparticles of the present invention has the advantages of high efficiency and simple operation process, and is very suitable for large-scale industrial production. It can not only significantly reduce production costs and improve production efficiency, but also expand the application scope of Janus materials and has good practical utilization value. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to fully understand the technical solutions and beneficial effects of the present invention, the following is further described in detail in conjunction with specific examples. It should be emphasized that the following examples are preferred embodiments of the present invention but not all, and these examples do not constitute any limitation to the present invention. Any simple improvements made on this basis will fall within the scope of protection of the present invention.
[0026] Example 1
[0027] 1 g of carboxylated nanocellulose, 12 g of isocyanatepropyltriethoxysilane, 50 g of deionized water, and 40 g of xylene were mixed and ultrasonically dispersed for 10 minutes. The mixture was then heated to 40°C for 4 hours and then centrifuged to obtain a solid. The solid was repeatedly washed with deionized water and then dried at 50°C for 24 hours to obtain isocyanate-based nanocellulose.
[0028] Weigh 50 g of a 20 wt % liquid butyl rubber xylene solution, then slowly drop a mixed solution of hydrogen peroxide and formic acid (the molar ratio of hydrogen peroxide, formic acid and double bonds in the liquid butyl rubber is 1:1:1), heat the resulting mixture to 40° C. and react for 6 hours, and finally remove the solvent to obtain epoxidized butyl rubber (EIIR).
[0029] 1 g of isocyanate-based nanocellulose was weighed and added to 10 g of epoxidized butyl rubber, and the mixture was heated to 190° C. at a rotation speed of 20 rpm for melt blending to obtain a Janus particle compatibilizer.
[0030] Weigh 1g of the Janus particle compatibilizer and add it to 30g of butyl rubber, mix well to obtain a composite material, mix the composite material with 70g of thermoplastic polyurethane, heat to 170°C for melt blending, and cool to obtain a thermoplastic polyurethane / butyl rubber blend.
[0031] Comparative Example 1
[0032] 30 g of butyl rubber and 70 g of thermoplastic polyurethane were mixed, the mixture was heated to 170° C. for melt blending, and after cooling, a thermoplastic polyurethane / butyl rubber blend was obtained.
[0033] Example 2
[0034] 10 g of carboxylated nanocellulose, 1 g of isocyanatepropyltriethoxysilane, 10 g of deionized water, and 10 g of xylene were mixed and ultrasonically dispersed for 25 minutes. The mixture was then heated to 50°C for a reaction of 5 hours, and then centrifuged to obtain a solid. The solid was repeatedly washed with deionized water and then dried at 60°C for 20 hours to obtain isocyanate-based nanocellulose.
[0035] 10 g of isocyanate-based nanocellulose was weighed and added to 10 g of epoxidized butyl rubber (prepared according to the above method or purchased from the market), and the mixture was heated to 170° C. at a rotation speed of 80 rpm for melt blending to obtain a Janus particle compatibilizer.
[0036] 3 g of the Janus particle compatibilizer was weighed and added to 30 g of butyl rubber, and mixed to obtain a composite material. The composite material was mixed with 70 g of thermoplastic polyurethane and heated to 190° C. for melt blending, and cooled to obtain a thermoplastic polyurethane / butyl rubber blend.
[0037] Comparative Example 2
[0038] 3 g of nanocellulose (CNC) was weighed and added to 30 g of butyl rubber, and mixed to obtain a composite material. The composite material was mixed with 70 g of thermoplastic polyurethane and heated to 190° C. for melt blending, and cooled to obtain a thermoplastic polyurethane / butyl rubber blend.
[0039] Example 3
[0040] 20 g of carboxylated nanocellulose, 20 g of isocyanatepropyltriethoxysilane, 100 g of deionized water, and 100 g of xylene were mixed and ultrasonically dispersed for 30 minutes, and then the mixture was heated to 70°C for 6 hours, and then centrifuged to obtain a solid. After repeatedly washing the solid with ethanol, it was placed at 50°C for 12 hours to obtain isocyanate-based nanocellulose.
[0041] 20 g of isocyanate-based nanocellulose was weighed and added to 20 g of epoxidized butyl rubber, and the mixture was heated to 230° C. at a rotation speed of 100 rpm for melt blending to obtain a Janus particle compatibilizer.
[0042] 5 g of the Janus particle compatibilizer was weighed and added to 30 g of butyl rubber, and mixed to obtain a composite material. The composite material was mixed with 70 g of thermoplastic polyurethane and heated to 240° C. for melt blending, and cooled to obtain a thermoplastic polyurethane / butyl rubber blend.
[0043] Example 4
[0044] 10 g of carboxylated nanocellulose, 12 g of isocyanatepropyltriethoxysilane, 50 g of deionized water, and 50 g of xylene were mixed and ultrasonically dispersed for 30 minutes. The mixture was then heated to 50°C for 5 hours and then centrifuged to obtain a solid. After repeatedly washing the solid with ethanol, it was dried at 60°C for 10 hours to obtain isocyanate-based nanocellulose.
[0045] 10 g of isocyanate-based nanocellulose was weighed and added to 10 g of epoxidized butyl rubber, and the mixture was heated to 180° C. at a rotation speed of 80 rpm for melt blending to obtain a Janus particle compatibilizer.
[0046] 3 g of the Janus particle compatibilizer was weighed and added to 30 g of butyl rubber, and mixed to obtain a composite material. The composite material was mixed with 70 g of thermoplastic polyurethane and heated to 180° C. for melt blending, and cooled to obtain a thermoplastic polyurethane / butyl rubber blend.
[0047] Example 5
[0048] 15 g of carboxylated nanocellulose, 10 g of isocyanatepropyltriethoxysilane, 100 g of deionized water, and 100 g of xylene were mixed and ultrasonically dispersed for 30 minutes, and then the mixture was heated to 60°C for reaction for 5 hours, and then centrifuged to obtain a solid. After repeatedly washing the solid with water, it was dried at 70°C for 12 hours to obtain isocyanate-based nanocellulose.
[0049] 15 g of isocyanate-based nanocellulose was weighed and added to 20 g of epoxidized butyl rubber, and the mixture was heated to 190° C. at a rotation speed of 100 rpm for melt blending to obtain a Janus particle compatibilizer.
[0050] 3 g of the Janus particle compatibilizer was weighed and added to 30 g of butyl rubber, and mixed to obtain a composite material. The composite material was mixed with 70 g of thermoplastic polyurethane and heated to 195° C. for melt blending, and cooled to obtain a thermoplastic polyurethane / butyl rubber blend.
[0051] In order to fully understand the performance of the thermoplastic polyurethane / butyl rubber blend samples prepared in each embodiment and comparative example, samples were taken for tensile strength, elongation at break, hardness, and thermal decomposition temperature tests, wherein the tensile strength, elongation at break, and hardness were measured in accordance with GB / T528-2009 and GB / T 531.1-2008, respectively. The thermal decomposition temperature test method is as follows: an appropriate amount of sample was heated from 30°C to 800°C at a heating rate of 10°C / min in a nitrogen atmosphere for thermal decomposition test.
[0052] The performance comparison table of the thermoplastic polyurethane / butyl rubber blend samples prepared in Examples 1-5 and Comparative Examples 1-2 is as follows:
[0053] Table 1 Performance comparison of different thermoplastic polyurethane / butyl rubber blend samples
[0054]
[0055] The following conclusions can be drawn from analyzing Table 1:
[0056] ① Comparative Example 1 corresponds to Example 1, and the difference between the two is that Example 1 adds a nanocellulose-based Janus particle compatibilizer, while Comparative Example 1 does not add any compatibilizer. The results show that the Janus particle compatibilizer in Example 1 can effectively improve the compatibility of the thermoplastic polyurethane / butyl rubber blend, and the tensile strength, elongation at break, hardness and heat resistance of the prepared composite material are all improved;
[0057] ②Comparative Example 2 corresponds to Example 2, and the difference between the two is that a nanocellulose-based Janus particle compatibilizer is added in Example 2, while unmodified nanocellulose is added in Comparative Example 2. The results show that the tensile strength, elongation at break, hardness and heat resistance of the blend prepared in Example 2 are all improved relative to those in Comparative Example 2. Analysis of the reasons suggests that the carboxyl and hydroxyl functional groups on the surface of unmodified nanocellulose are prone to form aggregates during the blending process, resulting in a decrease in the performance of the blend, that is, unmodified nanocellulose cannot be used as a compatibilizer for thermoplastic polyurethane / butyl rubber blends.
[0058] ③ Comparing Examples 3-5, it can be found that the amount of Janus particle compatibilizer in Example 3 is 5wt%, which is higher than 3wt% in Examples 4-5, resulting in the mechanical properties and heat resistance of the blend prepared in Example 3 being lower than those in Examples 4-5. This result shows that excessive compatibilizer may produce a stronger shielding effect at the interface, not only failing to produce effective molecular chain entanglement with the two-phase matrix, but also being unfavorable for stress transfer and improvement of heat resistance.
[0059] ④ By comparing Examples 4-5, it can be found that the usage ratio of isocyanatepropyltriethoxysilane and carboxylated nanocellulose in Example 4 is higher, which makes the mechanical properties and heat resistance of the blend better. This result shows that the high functionality of the Janus particle surface can effectively improve its compatibilization ability and ultimately improve the performance of the blended material.
Claims
1. A Janus particle based on nanocellulose, characterized in that: The Janus particles are specifically nanocellulose with isocyanate groups and butyl rubber modified at both ends respectively.
2. The method for preparing Janus particles according to claim 1, characterized in that The method comprises: mixing and reacting isocyanate-based nanocellulose and epoxidized butyl rubber to obtain nanocellulose-based Janus particles.
3. The method according to claim 2, characterized in that The preparation method of isocyanate-based nanocellulose is as follows: carboxylated nanocellulose, isocyanate propyltriethoxysilane and a solvent are uniformly mixed, the obtained mixture is heated for reaction, and then solid-liquid separation is performed to obtain isocyanate-based nanocellulose.
4. The method according to claim 3, characterized in that: The solvent is specifically a mixture of deionized water and xylene, and the mass ratio of the two is 10-100:10-100; the mass ratio of the carboxylated nanocellulose, isocyanate propyl triethoxysilane, and the solvent required for the reaction is 1-20:1-20:20-200.
5. The method according to claim 3, characterized in that: After the addition is completed, the raw materials are mixed evenly by ultrasound, and the reaction temperature of the mixture is 40-70°C.
6. The method according to claim 2, characterized in that: The mass ratio of isocyanate-based nanocellulose to epoxidized butyl rubber is 1-20:1-20.
7. The method according to claim 2, characterized in that: After the isocyanate-based nanocellulose and the epoxidized butyl rubber are mixed, they are heated to 170-230° C. for high-temperature melt blending while stirring, and then naturally cooled to room temperature to obtain nanocellulose-based Janus particles.
8. Use of the Janus particles according to claim 1 as a compatibilizer in a thermoplastic polyurethane-butyl rubber blend.
9. The use according to claim 8, characterized in that The specific method of the application is as follows: thermoplastic polyurethane or butyl rubber is mixed with the Janus particles, and then butyl rubber or thermoplastic polyurethane is added and heated to melt and blend, and then naturally cooled.
10. The use according to claim 9, characterized in that: The mass ratio of thermoplastic polyurethane to butyl rubber is (10-X):(X), and the value range of X is 1-4; the added amount of Janus particles is equivalent to 0.5%-5% of the total mass of thermoplastic polyurethane and butyl rubber, and the melt blending temperature is 170-240°C.
Citation Information
Patent Citations
A Janus compatibilizer for toughening epoxy resins in rubber and its preparation method
CN107603157B
Janus particle cross-linking agent and two-step preparation method and application thereof
CN118440533A